Portrait Of the Managerial Pattern of School Principal In Developing A Quality Culture Of High Achieving Islamic School - Muhamad Yasin (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
Mastery of managerial skills, ability and orientation to plan, organize, communicate, motivate, direct and monitor continuously is an effort to improve the quality of schools to achieve student achievement, both academic and non-academic. There are several Islamic schools in Kediri which are proven to produce both academic and non-academic achievements which can be used as quality references for other schools. In this research, the managerial patterns of school principals will be studied in developing a quality culture in Islamic schools from three aspects of management; planning, implementation, and evaluation. This research uses a qualitative-descriptive method and a phenomenological-naturalistic approach. The results of the research show that school principals in building a quality culture of achieving schools are: 1). Planning: establishing a vision and mission as quality guidelines, commitment to implementing SNP standard schools, a comfortable school service process, improving school quality as a result of a sustainable program; 2). Implementation: implementing the national curriculum and typical of the institution, educators and education staff who have appropriate qualifications, graduates are equipped with skills, there is representative infrastructure, transparent education management, the school has very close relations with the community, there are special services and learning support facilities. 3). Evaluation: carry out a self-evaluation of school performance based on transparency, accountability, efficiency and effectiveness, prepare a report on the results of the school's self-evaluation, and develop a priority scale for follow-up activities and programs.